ASSESSING HOW EDUCATION FOCUSED ON SUICIDE INFLUENCES GRADUATE STUDENTS’ VIEWS - Thompson, Emily; Brooks, Laura (International Research Journal of Sociology, Psychology and Anthropology, 2024)
Suicide occurs at alarming rates across the United States and rates are on the rise. The majority of those who attempt suicide report meeting with a medical or mental health provider in the six months prior to their attempt. Graduate programs that prepare social workers need to be prepared to offer adequate training to their students that include content about the needs of suicidal clients and survivors. The purpose of the study was to examine student perceptions of their readiness to work with clients experiencing suicidal ideations following completion of an elective course on suicide related issues. The researchers collected and analyzed data from narrative assignments completed by the participants and from focus groups with three cohorts of students. Results show participants (n=49) felt anxiety due to a lack of knowledge about what to do in suicide situations and felt unprepared to assess suicidality prior to the course. Upon course completion, they reported reduced anxiety and more comfort with the complexity surrounding suicidal client situations. The authors recommend that programs consider providing a course focused on suicide-related issues and/or provide specific examples of suicide related content in existing courses.